2016
DOI: 10.1002/smj.2492
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility as an employee governance tool: Evidence from a quasi‐experiment

Abstract: Research summary: This study examines whether companies employ corporate social responsibility (CSR) to improve employee engagement and mitigate adverse behavior at the workplace (e.g., shirking, absenteeism). We exploit plausibly exogenous changes in state unemployment insurance (UI) benefits from 1991 to 2013. Higher UI benefits reduce the cost of being unemployed and hence increase employees' incentives to engage in adverse behavior. We find that higher UI benefits are associated with higher engagement in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
261
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 384 publications
(268 citation statements)
references
References 142 publications
(220 reference statements)
6
261
0
1
Order By: Relevance
“…Green process innovation can prove a firm is acting with social responsibility [52][53][54]. These practices are perceived to be sincere by external stakeholders [55]. Firm's image is defined as the current image of the firm in the minds of the public [6].…”
Section: Green Process Innovation and Firm Imagementioning
confidence: 99%
“…Green process innovation can prove a firm is acting with social responsibility [52][53][54]. These practices are perceived to be sincere by external stakeholders [55]. Firm's image is defined as the current image of the firm in the minds of the public [6].…”
Section: Green Process Innovation and Firm Imagementioning
confidence: 99%
“…The role of for‐profit businesses in addressing social problems—climate change, disease, hunger, poverty, exploitation, and so on—is a topic of growing interest in the field of strategic management (Barney, ; George, Howard‐Grenville, Joshi, & Tihanyi, ; Mahoney, McGahan, & Pitelis, ). Building on an early emphasis on the ethical imperative for firms to recognize and take responsibility for the broader consequences of their actions (Freeman, ; Hinings & Greenwood, ; Stern & Barley, ), the literature has increasingly come to emphasize the strategic value of socially responsible actions (Dorobantu, Kaul, & Zelner, ; Flammer & Luo, ; McWilliams & Siegel, ). While this work provides strong evidence for a positive link between corporate social responsibility (CSR) and firm financial performance (Barnett & Salomon, ; Flammer, ; Henisz, Dorobantu, & Nartey, ; King & Lenox, ; Waddock & Graves, ), it is far from clear that such activities truly contribute to social welfare (Barnett, ; Jones et al, ; Kaul & Luo, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, it has been shown that CSR can help companies differentiate themselves from their foreign and local competitors (Fernandez‐Kranz & Santalo, ; Flammer, ) and from other employers (Flammer & Luo, ).…”
mentioning
confidence: 99%
“…In this vein, it has been shown that CSR can help companies differentiate themselves from their foreign and local competitors (Fernandez-Kranz & Santalo, 2010;Flammer, 2015b) and from other employers (Flammer & Luo, 2017). 10 In a seminal article, Spence (1973) shows that costly signals are more credible, as they are harder (i.e., costlier) to mimic.…”
mentioning
confidence: 99%